Motivating reluctant readers using the bibliotherapy technique: a case study in UiTM Melaka / Josephine Lourdunathan and Angeline Ranjethamoney Vijayarajoo - Josephine Lourdunathan; Angeline Ranjethamoney Vijayarajoo (Institute of Research, Development and Commercialization, 2006)
A literacy has become a widespread concern in our country. Our young generation has become a group of reluctant readers due to the learning environment, among other factors. The learning environment focuses on academic achievement and most reading outcomes expected are confined only to academic success, neglecting the aesthetic appreciation of texts for its own sake. The researchers set out on a quest to find ways of motivating adolescent students in the ESL classroom, to begin to enjoy the pleasure of reading and through this, the other benefits of reading which they have deprived themselves of : knowledge, developing a personality, becoming a more interesting and wholesome individual, an asset to the community and workplace. The researchers believed that reluctant readers can be reached, give motivation and guidance. It is this that formed the basis of this current research which aimed at investigating the potential role of bibliotherapy, in encouraging unmotivated young adults to read extensively. Basically, bibliotherapy is a process/treatment which focuses on personalized and meaningful reading. A case study was conducted with five participants from the Pre-Tesl group of UiTM Melaka. Methodology included questionnaire, face-to-face interviews and log sheet.